IMPLEMENTATION OF OUTCOME-BASED EDUCATION (OBE) IN CHEMICAL ENGINEERING PROGRAMME: REVIEW ON STUDENTS’ PERFORMANCE IN DESIGN PROJECT COURSE - Mohamad Sufian So’aib; Hamizura Hassan; Chang Siu Hua; Nur Fadzeelah Abu Kassim, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Outcome-based education (OBE) is an effective goal-driven method to measure the outcomes of a curriculum. Its implementation in Bachelor of Chemical Engineering Programme at UiTM Pulau Pinang ensures the integrity of the assessments on various components of the course and improves the course delivery methods and student’s expected attributes. Implementation of OBE throughout 2020 to 2023 coincided with tumultuous years of 2020 and 2021 where COVID19 restrictions impacted many learning activities. Thus, using Design Project (DP) as a case study, a review on students’ performance throughout this period was conducted based on the course outcome (CO) and programme outcome (PO) which were mapped to various components of the course. Generally, students’ performance in DP course were not significantly different throughout 2020 to 2023 period, while their CO/PO attainments exceeded minimum target of 50% across the entire CO/PO attributes, with only one instance in 2020 where a CO/PO score did not meet the minimum threshold. Additionally, students’ own assessment through questionnaires strongly suggested their perceived attainments in all COs. In conclusion, steady performance of students during implementation of the DP course throughout 2020 to 2024 demonstrated the robustness of OBE assessment method.